Engaging Stakeholders in the Design of One Health Surveillance Systems: A Participatory Approach - Bordier, Marion; Goutard, Flavie Luce; Antoine-Moussiaux, Nicolas; Pham-Duc, Phuc; Lailler, Renaud; Binot, Aurelie (Frontiers in Veterinary Science, 2021)
Many One Health surveillance systems have proven difficult to enforce and sustain, mainly because of the difficulty of implementing and upholding collaborative efforts for surveillance activities across stakeholders with different values, cultures and interests. We believe that only the early engagement of stakeholders in the development of a One Health surveillance system can create an environment conducive to the emergence of collaborative solutions that are acceptable, accepted and therefore implemented in sustainable manner. To this end, we have designed a socio-technical framework to help stakeholders develop a common vision of their desired surveillance system and to forge the innovation pathway towards it. We implemented the framework in two case studies: the surveillance of antibiotic resistance in Vietnam and that of Salmonella in France. The socio-technical framework is a participatory and iterative process that consists of four distinct steps: (i) definition of the problem to be addressed, (ii) co-construction of a common representation of the current system, (iii) co-construction of the desired surveillance system, (iv) identification of changes and actions required to progress from the current situation to the desired situation. In both case studies, the process allowed workshop participants with different professional cultures and expectations regarding One Health surveillance to gain mutual understanding and to reconcile their different perspectives to design the pathway towards their common vision of an ideal surveillance system. While the proposed framework is structured around four essential steps, its application can be tailored to the context –including the maturity of the surveillance system-, the knowledge gained and the receptivity demonstrated by participants during the process. Workshop facilitation and representativeness of participants are key for the success of the process. While our approach lays the foundation for the further implementation of the desired One Health surveillance system provides, it provides no guarantee that the proposed actions will actually be implemented and bring about the required changes. The engagement of stakeholders in a participatory process must be sustained in order to ensure the implementation of co-constructed solutions and evaluate their effectiveness and impacts..